ANALISIS EKONOMI SYARIAH: SUN LIFE ASURANSI SALAM HIJRAH AMANAH PRO DI BANK MUAMALAT - Wanala Abdillaika Martiwi; Eny Latifah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyse the implementation of Sun Life Insurance’s Salam Hijrah Amanah Pro at Bank Muamalat Indonesia KCP Lamongan and assess its compliance with Islamic economic principles. This study uses a qualitative descriptive method with a case study approach. Data was obtained trought observation, interviews, and documentation, then analysed using data reduction, ata presentation, and conslusion drawing techniques. The relust of the study indicate that the product is intended for prospective pilgrims who have scured a place on a pilgrimage and are still in the waiting period. This product uses a tabarru’ contract, wich is a mutual assistance contract between participants in facing risk. From an Islamic economic perspective, the application of this product is considered to be in accordance with sharia principles becauses it avoids the elements of usury, gambling, and gharar. In addition, its implementation also reflects the values of fairness, transparency, and social responsbility. Thus, the Sun Life Salam Hijrah Amanah Pro Insurance product can be used as a model of synergy between the banking sector and the Islamic insurance industry to strengthen Islamic finance based on ethical values and fairness.